Immunohistochemistry for diagnosis and prognosis of breast cancer: a review. (17th February 2020) - Bonacho, T.; Rodrigues, F.; Liberal, J.
ABSTRACT: Breast cancer is the most prevalent malignant tumor and main oncologic cause of mortality in women. Although most diagnosis of breast pathology is accomplished using hematoxylin and eosin stained sections, some cases require immunohistochemistry for proper evaluation. We investigated the latter cases including distinctions between ductal and lobular carcinoma, in situ and invasive carcinoma, typical ductal hyperplasia and atypical ductal hyperplasia/ductal carcinoma in situ, papillary and spindle cell lesion assessment, metastasis evaluation, and assessment of prognostic and therapy markers. E-cadherin is used to differentiate ductal and lobular carcinoma; 34βE12, CK8, p120 catenin and β-catenin also produce consistent results. Myoepithelial cell (MEC) stains are used to evaluate in situ and invasive carcinoma; calponin, smooth muscle myosin heavy chain and p63 are sensitive/specific markers. 34βE12 and CK5/6 are positive in ductal hyperplasia, which enables its differentiation from atypical ductal hyperplasia and ductal carcinoma in situ. CK 5/6, ER and MEC markers are consistent options for evaluating papillary lesions. Spindle cell lesions can be assessed using β-catenin, SMA, CD34, p63, CKs and hormone receptors. It is important to differentiate primary carcinomas from metastases; the most commonly used markers to identify breast origin include mammaglobin, GCDFP-15, GATA3 and ER, although none of these is completely sensitive or specific. Immunohistochemistry can be used to evaluate central prognostic and predictive factors including molecular subtypes, HER2, hormone receptors, proliferation markers (Ki-67) and lymph-vascular invasion markers including ERG, CD31, CD34, factor VIII and podoplanin. Owing to the complexity of mammary lesions, diagnosis also depends on each particular situation, evaluation of cytological characteristics revealed by immunochemistry and correlation with histological findings.